Thermochromic SmNiO3-δ thin films deposited by magnetron sputtering and crystallized by soft-annealing in air. (September 2022) - Fernández-Gutiérrez, Zil; Pilloud, David; Bruyère, Stéphanie; Didelot, Aurélien; Kharkhan, Daria N.; Barrat, Silvère; Capon, Fabien
Abstract: Samarium nickelate (SmNiO3 ) exhibits a metal-insulator transition (MIT) around 120 °C and therefore appears to be an excellent candidate for a new generation of thermochromic solar absorbers. Nevertheless, this kind of perovskite is classically obtained under extreme conditions to stabilize the metastable Ni 3+ oxidation state. Here, we show that SmNiO3-δ thin films can be synthesized under soft-annealing as the habitual orthorhombic distorted perovskite structure. The layers were deposited by reactive magnetron co-sputtering and subsequently annealed for crystallization for 2 h at 500 °C in air. Structural characterization was carried out using X-ray diffraction (XRD) and transmission electron microscopy (TEM) techniques, while optical and electrical properties were determined by Fourier transform infrared spectroscopy (FTIR) and the four-point probe method, respectively. The Ni 3+ ion was confirmed by Electron energy loss spectroscopy (EELS). Finally, reversible thermochromic behavior was observed with an MIT temperature estimated at 138 °C and an IR contrast of 19%. Graphical abstract: Image, graphical abstract